Unsupervised Learning: Difference between revisions

Line 87: Line 87:
We can maximize each <math>Q^{(i)}</math> independently.<br>
We can maximize each <math>Q^{(i)}</math> independently.<br>
Taking the derivative wrt Q we get:<br>
Taking the derivative wrt Q we get:<br>
<math>
<math display="block">
\begin{aligned}
\frac{\partial}{\partial Q^{(i)}_{(j)}} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)
\frac{\partial}{\partial Q^{(i)}_{(j)}} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)
</math><br>
&= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - Q \frac{Q}{P(x^{(i)}, z^{(i)}=j;\theta)} (P(x^{(i)}, z^{(i)}=j;\theta))(Q^{-2}) + \beta\\
<math>
&= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - 1 + \beta \\
= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - Q \frac{Q}{P(x^{(i)}, z^{(i)}=j;\theta)} (P(x^{(i)}, z^{(i)}=j;\theta))(Q^{-2}) + \beta
&= 0\\
</math>
\implies Q^{(i)}_{(j)} &= (\frac{1}{exp(1-\beta)})P(x^{(i)}, z^{(i)}=j;\theta)
</math><br>
\end{aligned}
<math>
= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - 1 + \beta = 0
</math><br>
<math>
\implies Q^{(i)}_{(j)} = (\frac{1}{exp(1-\beta)})P(x^{(i)}, z^{(i)}=j;\theta)
</math><br>
</math><br>
Since Q is a pmf, we know it sums to 1 so we get the same result replacing <math>(\frac{1}{exp(1-\beta)})</math> with <math>P(x^{(i)}</math>
Since Q is a pmf, we know it sums to 1 so we get the same result replacing <math>(\frac{1}{exp(1-\beta)})</math> with <math>P(x^{(i)}</math>